2022
DOI: 10.14233/ajchem.2023.24058
|View full text |Cite
|
Sign up to set email alerts
|

Psidium guajava L. (Common Guava) Peel, Pulp and Leaves as Natural Sources of Antioxidants, Antimicrobials and Photoprotective Agents for Development of Sun Protection Cosmeceuticals

Abstract: Sunscreens with natural ingredients for skin care become a new trend in cosmetology as it protects skin against photo-aging and dermatologic disorders. Therefore, the goal of this study was to evaluate the antioxidant, antimicrobial and photoprotective properties of methanolic extracts of leaves, peel and pulp of Psidium guajava L. to investigate their potentials to be used as sources of cosmeceutical ingredients for sun protection. Chemical constituents of the plant parts were extracted into methanol by macer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
1
0
0
Order By: Relevance
“…Jassal et al [42] reported that the IC 50 of DPPH radical scavenging of guava leaf essential oil was 445 ± 0.001 µg/mL which was lower than our results. Dewage et al [43] studied the antioxidant activity of the guava leaf through DPPH assay and the resultant IC 50 was 90.07 ± 0.73 µg/mL and when compared to our results with methanolic extract (78.93 ± 0.46 µg/mL) it was very low. Similarly, Jani et al [27] recorded the DPPH radical scavenging capacity of Psidium guajava with an IC 50 of 45.52 µg/mL.…”
Section: Free Radical Scavenging Potential Of Guava Cultivarssupporting
confidence: 46%
“…Jassal et al [42] reported that the IC 50 of DPPH radical scavenging of guava leaf essential oil was 445 ± 0.001 µg/mL which was lower than our results. Dewage et al [43] studied the antioxidant activity of the guava leaf through DPPH assay and the resultant IC 50 was 90.07 ± 0.73 µg/mL and when compared to our results with methanolic extract (78.93 ± 0.46 µg/mL) it was very low. Similarly, Jani et al [27] recorded the DPPH radical scavenging capacity of Psidium guajava with an IC 50 of 45.52 µg/mL.…”
Section: Free Radical Scavenging Potential Of Guava Cultivarssupporting
confidence: 46%
“…The highest AAI in all fractions was given by the G3 treatment, compared to the control (G0). Dewage et al (2022) reported that the methanol extract of Psidium guajava fruit in India gave the highest antioxidant activity results compared to other plants with an IC50 value of 1.33 mg/mL. Antioxidant activity of crystal guava with G0 and G3 treatments was higher than that of tomatoes from Toraja (Mu'nisa, 2012).…”
Section: Dpph Radical Scavenging Activity Of Crystal Guava (Psidium G...mentioning
confidence: 99%
“…A disk diffusion method is used to measure the antimicrobial property of two concentrations of ethanol-extracted guava extract against S. aureus. This method is known to be the most widely used method for determining antimicrobial resistance around the world [9]. The procedure involves seeding a lawn of bacteria on the surface of an agar medium with paper disks saturated with the antimicrobial compound.…”
Section: Instrumentsmentioning
confidence: 99%